Reporting of blood pressure levels and self-monitoring practices (2023)
Background Routine blood pressure (BP) self-monitoring is recommended for patients already diagnosed with hypertension. How often these patients can report their BP levels is unknown, particularly in low-and-middle income countries. Methods We surveyed (January 2021 to May 2022) representative samples of patients with established diagnosis of hypertension from 3 health care networks (involving 74 outpatient clinics) and 2 university hospitals in Bogotá, Colombia. Trained health care professionals conducted a telephone survey including questions on demographics, medical history, and general understanding about hypertension and its potential complications. The outcome variables were the self-report of participant’s BP levels (primary) and monitoring practices among participants. Results Out of 2609 consecutively contacted patients sampled from institutional records, 2323 were invited and 1566 (mean age 66.5, SD=12.1 years, 74.4% females, 64.0% living low socio-economic strata) gave consent to participate. While 66% of participants had over 5 years of diagnosis, 39.5% had most (?60%) of their follow-up visits with the same doctor. Overall, 645 (41.5%, 95%CI 39.1 -43.9) participants reported their BP levels. This proportion was independent of time from diagnosis, but higher among those of younger age, living in higher socio-economic strata, having more years of education and using more information technologies. Also, more patients reported their BP levels if seen?60% of the times by the same physician (43.4% Vs. 36.7%). Those reporting closer BP self-monitoring more often used electronic devices, received 2+medications, and had better knowledge about hypertension. Conclusion A minority of hypertensive patients seen in Bogotá were aware of their own BP levels. Those in such capacity were in a better social position, more often seen by the same doctor, knew their condition better and handled more complex treatments. Hypertensive patients from Bogotá may benefit from a more continuous medical care, patient education programs and promoting BP home monitoring.